Pogledi na slovenščino kot neprvi jezik v zgodnjem izobraževanju (University of Maribor Press, 2021)
Views on Slovene as a Non-first Language in Early education. The scientific monograph on teaching Slovene as a second and foreign language (DTJ/SFL) for immigrant children, disadvantaged due to their linguistic and cultural peculiarities compared to their peers, is designed to be transdisciplinary and brings scientific papers in the humanistic and social sciences, natural sciences and arts, referring to teaching Slovene as a second and foreign language from different perspectives. The monograph contains 16 chapters divided to 3 contentually related parts: Teaching Language and Interculturality, which presents interculturality, didactic principles, developmental characteristics of children and methods of working with immigrant children; the second part of the monograph, entitled Language about Language, contains chapters on development and promotion of linguistic and intercultural competences; the third part, entitled Language of Different Fields of Activity and Subject Areas, presents chapters related to mathematics, science and arts.